Investigating the Anti-Inflammatory, Antioxidant and Apoptotic Protein Inhibition Study of Berberine on Diabetic Retinopathy in Rats - Wang, Lihui; Fei, Wei; Qin, Chongjuan; Zhang, Jing (Indian Journal of Pharmaceutical Education and Research)
Background Globally, Diabetic Retinopathy (DR) is a leading cause of vision loss. This disease, which impacts the microvasculature of the retina, is brought on by the oxidative stress linked to diabetes. Several studies have shown the anti-diabetic properties of the plant-derived phytochemical "Berberine". However, there is a limited amount of research available on its effects, specifically on Diabetic Retinopathy (DR). Objectives The primary aim of the present investigation is to assess the impact of berberine on DR in rats by examining its underlying influence on oxidative stress, inflammation and programmed cell death. Materials and Methods The current study effectively established a rat model of diabetic retinopathy utilizing Streptozotocin (STZ). The diabetic rats were treated for 12 weeks and evaluated for inflammatory markers (TNF-α, VEGF), antioxidant markers (superoxide, dismutase, catalase and glutathione) and apoptosis markers (Bcl-2, Bax, Cleaved-caspase-3). Results The results demonstrated that Berberine treatment had a significant hypoglycemic index when compared to the diabetic group. Berberine therapy significantly reduced high levels of pro-inflammatory cytokines (TNF-α and VEGF) in the diabetic retina. Berberine also was effective in modulating the antioxidant enzymes and bringing their concentrations to acceptable levels. Berberine treatment also reduced the apoptosis of diabetic mice retina by reducing the elevated ROS level caused by high glucose and reduced the ratio of Bax/Bcl-2 and the expression of cleaved caspase-3. Conclusion Based on the findings, it is possible to infer that Berberine has potential as a pharmacological candidate for the prevention of DR.
Keywords: Diabetic retinopathy; Apoptosis; Anti-inflammatory; Alloxan; Cytokines; Antioxidant.